Consequences of Severe Iodine Deficiency in Pregnancy: Evidence in Humans - Toloza, Freddy J. K.; Motahari, Hooman; Maraka, Spyridoula (Frontiers in Endocrinology, 2020)
Iodine is a necessary micronutrient for the production of thyroid hormones and normal human development. Despite the significant worldwide strategies for the prevention and control of iodine deficiency, it is still a prevalent public health issue, especially in pregnant women. Severe iodine deficiency during pregnancy and neonatal period is associated with many major and irreversible adverse effects, including an increased risk of pregnancy loss and infant mortality, neonatal hypothyroidism, cretinism, and neuropsychomotor retardation. We will review the impact of severe iodine deficiency on maternofetal, neonatal, and offspring outcomes. We will also discuss its epidemiology, classification of iodine deficiency severity, and current recommendations to prevent iodine deficiency in childbearing age and pregnant women.